Pacific delights - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The Staples We Eat. CTA/Secretariat of the Pacific Community co-publication. 1999. 102 pp. ISBN 982 203 695 7. CTA number 959. 10 credit points.